MODERNISASI BISNIS UMKM DENGAN IMPLEMENTASI TEKNOLOGI CLOUD DI KOTA PADANG - Heri Yanto (Jurnal Ipteks Terapan, 2020)
Modernization in the field of umkm in the city of Padang is very much needed, considering the data from the Department of Cooperatives and Micro, Small and Medium Enterprises (UMKM) in the city of Padang in 2018 as many as 10,211 umkm in the city of Padang have not yet been integrated with information systems, the perpetrators of the umkm currently only utilize social media as a promotion which, according to the researchers, has not been able to maximize the sales process, there are still many umkm actors who do not use promotional media at the small-end level. Because umkm takes an important role as the driving wheel of the regional economy, even to the national axis, by integrating Web service on the marketing of souvenirs typical Padang can maximize the promotion process. By utilizing the integrated web service, the main obstacle is in the field of storage that requires no small cost. Cloud computing technology is the answer, in this study the author uses owncloud as a storage service, so the web as a display service for souvenirs typical of Padang and owncloud as a storage medium that has upload, download, and data sharing features.